Peeking into the world of shyness : a series of illustrated books - Tan, Wan Wen (2017)
In a tell-all society where outgoing individuals appear to be socially preferred, shy individuals are expected to build up their confidence and to ‘get out of their shell’. However, the difficulties that they face are more than just being tongue-tied but a series continuous struggle of self-evaluation, self-criticism and self-consciousness. The lack of empathy for shy individuals often results in the misunderstanding and lack of emotional support for them, leaving to fend for themselves in a world where outgoing characteristics are socially preferred. It does not help that shy individuals experience constant self-doubt and back away from what they fear.